1997
DOI: 10.1093/emboj/16.5.1114
|View full text |Cite
|
Sign up to set email alerts
|

A novel inhibitor of cap-dependent translation initiation in yeast: p20 competes with eIF4G for binding to eIF4E

Abstract: In the yeast Saccharomyces cerevisiae a small protein named p20 is found associated with translation initiation factor eIF4E, the mRNA cap-binding protein. We demonstrate here that p20 is a repressor of cap-dependent translation initiation. p20 shows amino acid sequence homology to a region of eIF4G, the large subunit of the cap-binding protein complex eIF4F, which carries the binding site for eIF4E. Both, eIF4G and p20 bind to eIF4E and compete with each other for binding to eIF4E. The eIF4E-p20 complex can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
152
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(158 citation statements)
references
References 44 publications
6
152
0
Order By: Relevance
“…Our data corroborate the previous hypothesis that p20 is a functional analogue of 4E-BP1, as suggested by different levels of p20 phosphorylation under various growth conditions (17). Furthermore, recent biochemical data have demonstrated that p20 acts similarly to 4E-BP1 in competing with eIF4G for binding to eIF4E (40). In agreement with these data, the absence or the overexpression of p20 significantly affect the growth of mutants of the cap-binding complex, including eIF4E, eIF4G and eIF4B.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our data corroborate the previous hypothesis that p20 is a functional analogue of 4E-BP1, as suggested by different levels of p20 phosphorylation under various growth conditions (17). Furthermore, recent biochemical data have demonstrated that p20 acts similarly to 4E-BP1 in competing with eIF4G for binding to eIF4E (40). In agreement with these data, the absence or the overexpression of p20 significantly affect the growth of mutants of the cap-binding complex, including eIF4E, eIF4G and eIF4B.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, deletion of CAF20 in cdc33-1 and cdc33-42 mutants did not suppress their growth defect as strongly as expected for a negative regulator that interacts directly with eIF4E. This is in agreement with the reduced interaction observed between these alleles of eIF4E and p20 (40). Nevertheless, overexpression of p20 might favor eIF4E-p20 complex formation, explaining the drastic reduction in the growth rate of the cdc33 mutants.…”
Section: Discussionsupporting
confidence: 67%
“…A central region of eIF4G (eIF4G1 ) binds to eIF4E on the opposite face to the 59 cap interaction ( Figure 6B). The eIF4E-4G binding interface overlaps with the surface important for binding 4E-binding proteins (4E-BPs) Caf20 and Eap1 that inhibit eIF4F assembly by competing with eIF4G to bind eIF4E (Altmann et al 1997;Ptushkina et al 1998;Cosentino et al 2000).…”
Section: Mrna Recruitment Of the 43s Picmentioning
confidence: 99%
“…However this interaction is inhibited by a small family of 4E binding proteins (4E-BPs) which can compete with eIF4G for binding to eIF4E Haghighat et al, 1995;Altmann et al, 1997;Matsuo et al, 1997). The extent of complex formation between the best studied of these proteins, 4E-BP1 (also known as PHAS-I) (Lawrence and , and eIF4E is regulated by the phosphorylation of 4E-BP1 (Graves et al, 1995;Von Manteu el et al, 1996;Brunn et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…As a result rapamycin inhibits cap-dependent initiation (Beretta et al, 1996a,b), as well as antagonizing increases in protein synthesis brought about by mitogenic stimuli . In some eukaryotic systems, notably the yeast Saccharomyces cerevisiae, rapamycin also inhibits the basal rate of protein synthesis (Barbet et al, 1996), although it is not yet clear whether the same mechanisms are responsible for the e ects of rapamycin in yeast and mammalian cells (Altmann et al, 1997;Thomas and Hall, 1997). Enhancement of protein synthesis at the translational level by mitogens is also associated with the increased phosphorylation of eIF4E at position Ser 209 (Joshi et al, 1995;Flynn and Proud, 1995), as well as the phosphorylation of eIF4G itself (Morley and Pain, 1995a,b).…”
Section: Introductionmentioning
confidence: 99%